6+5x-6x=-2

Simple and best practice solution for 6+5x-6x=-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6+5x-6x=-2 equation:


Simplifying
6 + 5x + -6x = -2

Combine like terms: 5x + -6x = -1x
6 + -1x = -2

Solving
6 + -1x = -2

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + -1x = -2 + -6

Combine like terms: 6 + -6 = 0
0 + -1x = -2 + -6
-1x = -2 + -6

Combine like terms: -2 + -6 = -8
-1x = -8

Divide each side by '-1'.
x = 8

Simplifying
x = 8

See similar equations:

| 24x^2+92x+80= | | 15x+6=12x+4 | | 3cos^2x+5sinx=4 | | 3x^2-29x-7=0 | | 1.5(x+8)=7.2+.9x | | 9.75-18=5.25 | | 4n^2-24n= | | 2.5x-15=12.5 | | q+-4=12 | | B+2.35=9.78+b+7.22 | | -10x-16y=-18 | | 4x^2-20x+21= | | 2x-10+x-40=180 | | x^2+42=70 | | 5-3x=-8x+5 | | 0=-x^2+13x-36 | | 2x-(x+1)=-2x+21 | | 6a^2-31a+28= | | h(h-1)/2h | | (4/5)*(1/6)= | | -2x+17=-13 | | (6/5x)-(8/5) | | 2ln(x)-3=-1 | | 2x-x=x-x+9 | | X=(6/5)x-(8/5) | | 2+10x=32 | | (6/5)x-(8/5) | | X=4(-8-5) | | (6y-14)/2 | | -y/4-12=-28 | | -6x-2=y | | |1/4x-2|=4 |

Equations solver categories